Fluorescence enhancement from single gold nanostars: towards ultra-bright emission in the first and second near-infrared biological windows. Issue 33 (14th August 2018) - Theodorou, Ioannis G.; Jiang, Qianfan; Malms, Lukas; Xie, Xiangyu; Coombes, R. Charles; Aboagye, Eric O.; Porter, Alexandra E.; Ryan, Mary P.; Xie, Fang
Abstract : Single-particle metal enhanced fluorescence from colloidal gold nanostars (AuNSs) enables super bright fluorescence from biologically relevant near-infrared fluorophores. Abstract : Gold nanostars (AuNSs) are promising agents for the development of high-performance diagnostic devices, by enabling metal enhanced fluorescence (MEF) in the physiological near-infrared (NIR) and second near-infrared (NIR-II) windows. The local electric field near their sharp tips and between their branches can be enhanced by several orders of magnitude, holding great promise for large fluorescence enhancements from single AuNS particles, rather than relying on interparticle coupling in nanoparticle substrates. Here, guided by electric field simulations, two different types of AuNSs with controlled morphologies and plasmonic responses in the NIR and NIR-II regions are used to investigate the mechanism of MEF from colloidal AuNSs. Fluorophore conjugation to AuNSs allows significant fluorescence enhancement of up to 30 times in the NIR window, and up to 4-fold enhancement in the NIR-II region. Together with other inherent advantages of AuNSs, including their multispike morphology offering easy access to cell membranes and their large surface area providing flexible multifunctionality, AuNS are promising for the development of in vivo imaging applications. Using time-resolved fluorescence measurements to deconvolute semi-quantitatively excitation enhancement from emission enhancement, we show that a combination of enhanced excitation and an increased radiative decay rate, both contribute to the observed large enhancement. In accordance to our electric field modelling, however, excitation enhancement is the component that varies most with particle morphology. These findings provide important insights into the mechanism of MEF from AuNSs, and can be used to further guide particle design for high contrast enhancement, enabling the development of MEF biodetection technologies.